2022
DOI: 10.1088/1755-1315/1079/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced vibration analysis of a prototype pump-turbine runner during turbine start-stop transient process

Abstract: Recently more start-stops per day of the pump-turbine units are required by the power grid for load regulation. During the turbine start-up and shut-down transient processes, the flow and pressure of the prototype pump-turbine change dramatically at different guide vane opening angles. The extremely unsteady pressure fluctuation in the flow passages can induce large deformation, stress concentration, and strong vibration of the pump-turbine runner. Therefore, it is significantly important to study the unsteady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[21,22]. Researchers have further confirmed the reliability of the numerical investigation according to the field measurement data for the turbine start-up of the pump-turbine units [23,24]. The results show that under the condition of limited computational resources, selecting key time points for static calculations is an efficient means to analyze the flow characteristics of the unit during the transient process.…”
Section: Introductionmentioning
confidence: 75%
“…[21,22]. Researchers have further confirmed the reliability of the numerical investigation according to the field measurement data for the turbine start-up of the pump-turbine units [23,24]. The results show that under the condition of limited computational resources, selecting key time points for static calculations is an efficient means to analyze the flow characteristics of the unit during the transient process.…”
Section: Introductionmentioning
confidence: 75%
“…He [12][13][14] et al took the clearance flow into the fluid calculation and successfully simulated the resonance curves of the runner start-up process. Zhou [15] et al studied the stress characteristics of the runner during the start-stop process, and found that the location of the maximum stress is transferred at different stages of the start-stop process. Biner [16,17] studied the stress and damage of a variable speed pump-turbine during start-up, and pointed out that the total damage can be reduced by 7.7 times if applying the variable speed best efficiency point (BEP) tracking strategy.…”
Section: Introductionmentioning
confidence: 99%